Methanogen activity and microbial diversity in Gulf of Cádiz mud volcano sediments - Webster, Gordon; Cragg, Barry A.; Rinna, Joachim; Watkins, Andrew J.; Sass, Henrik; Weightman, Andrew J.; Parkes, R. John (Frontiers in Microbiology, 2023)
The Gulf of Cádiz is a tectonically active continental margin with over sixty mud volcanoes (MV) documented, some associated with active methane (CH4) seepage. However, the role of prokaryotes in influencing this CH4 release is largely unknown. In two expeditions (MSM1-3 and JC10) seven Gulf of Cádiz MVs (Porto, Bonjardim, Carlos Ribeiro, Captain Arutyunov, Darwin, Meknes, and Mercator) were analysed for microbial diversity, geochemistry, and methanogenic activity, plus substrate amended slurries also measured potential methanogenesis and anaerobic oxidation of methane (AOM). Prokaryotic populations and activities were variable in these MV sediments reflecting the geochemical heterogeneity within and between them. There were also marked differences between many MV and their reference sites. Overall direct cell numbers below the SMTZ (0.2-0.5 mbsf) were much lower than the general global depth distribution and equivalent to cell numbers from below 100 mbsf. Methanogenesis from methyl compounds, especially methylamine, were much higher than the usually dominant substrates H2/CO2 or acetate. Also, CH4 production occurred in 50% of methylated substrate slurries and only methylotrophic CH4 production occurred at all seven MV sites. These slurries were dominated by Methanococcoides methanogens (resulting in pure cultures), and prokaryotes found in other MV sediments. AOM occurred in some slurries, particularly, those from Captain Arutyunov, Mercator and Carlos Ribeiro MVs. Archaeal diversity at MV sites showed the presence of both methanogens and ANME (Methanosarcinales, Methanococcoides, and ANME-1) related sequences, and bacterial diversity was higher than archaeal diversity, dominated by members of the Atribacteria, Chloroflexi, Proteobacteria, Planctomycetes, Firmicutes and Aminicenantes. Further work is essential to determine the full contribution of Gulf of Cádiz mud volcanoes to the global methane and carbon cycles.